2017
DOI: 10.1016/j.trac.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of exogenous VOCs as a novel in vitro diagnostic technique for the detection of pathogenic bacteria

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In a study on VOC profiles in Campylobacter jejuni positive fecal samples, it was found that the presence of one specific VOC was positively associated with C. jejuni [8]. Another study demonstrated the absence of two types of VOCS were strongly associated with C. jejuni, as listed in Table 2 [10].…”
Section: Other Infectious Diseasesmentioning
confidence: 99%
“…In a study on VOC profiles in Campylobacter jejuni positive fecal samples, it was found that the presence of one specific VOC was positively associated with C. jejuni [8]. Another study demonstrated the absence of two types of VOCS were strongly associated with C. jejuni, as listed in Table 2 [10].…”
Section: Other Infectious Diseasesmentioning
confidence: 99%
“…Our aim was to therefore develop a rapid test for the detection of Pseudomonas and Burkholderia from CF patient sputum samples, utilising balanyl aminopeptidase activity. We have previously identied that using targeted enzyme substrates, a unique exogenous volatile organic compound can be liberated and detected using either static headspace-solid phase micro-extraction-gas chromatography-mass spectrometry, SHS-SPME-GC-MS [23][24][25][26] or static headspace multicapillary column-gas chromatographyion mobility spectrometry, SHS-MCC-GC-IMS. 27 The use of exogenous volatile organic compounds (VOCs) to distinguish 7 Gram-positive from 15 Gram-negative bacteria using the enzyme substrates 2-amino-N-phenylpropanamide (to liberate the VOC aniline) and 2-amino-N-(4-methylphenyl)propanamide (to liberate the VOC p-toluidine) has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…VOC are the gaseous carbon-based organic chemicals and products of metabolic (patho-)physiological processes in the human body, which can be detected in various bodily excrements (e.g., exhaled breath, urine and feces). Fecal VOCs are considered to reflect the gut microbiota composition, function and interactions with the host [ 1 , 2 ]. Consequently, fecal VOC analysis is considered to be a powerful non-invasive diagnostic tool for gastrointestinal diseases, such as NEC and IBD, in which the intestinal microbiota alterations play an etiological role [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%